Last Year at Betty and Bob's An Actual Occasion - Doruff, Sher (punctum books, 2021)
"Last Year at Betty and Bob's: An Actual Occasion is the third in a series of three novellas emerging from a writing practice that taps the cusp of consciousness between dreaming and waking. An Actual Occasion revisits the viral transitioning of the becoming rat-woman from Last Year at Betty and Bob's: A Novelty (vol. 1 in the trilogy). The adventure focuses on the Gritta's, a gang of artists on retreat in the Dolomite Mountains, as they engage with the idiosyncratic, keeper of the keys, Roberta. Her other-worldly Café Arcadia, a magical cathedral of voluminous aphorism, is an archival refuge and durational homage to Benjaminian storytelling. This futurist fairy-tale is tinged with a curious mix of 19th-century feminist idioms and a queer, post-pandemic sanguinity."